STUDENTS’ MOTIVATION ON LEARNING ENGLISH AT TOEFL PROGRAM OF ELFAST ENGLISH COURSE IN PARE - SUGEHA, ANISA ZUHRIA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Key words: motivation, instrumental motivation, integrative motivation, TOEFL Program, ELFAST English Course.Nowadays, mastering a foreign language is important in order to adjust it with globalization era. In second language learning, there are some factors which influence the learners to be succesed in acquiring a foreign language. One of them is motivation.  Motivation is the reason why people do something based on their desire.This study was aimed to answer three problems of study namely: (1) What arethe types of motivation used by the students at TOEFL Program of ELFAST EnglishCourse in Pare? (2) What is the most dominant motivation in learning English of thestudents at TOEFL Program of ELFAST English Course in Pare? and (3) Is there any significant relationship between motivation used by the students at TOEFL Program of ELFAST English Course in Pare and their TOEFL scores?.In this study, the writer used Gardner’s theory (1985) about motivatio.In this study, the writer used descriptive quantitative approach. The instrument used to investigate motivation is AMTB questionnaire designed by Gardner (1985). The data sources of this study were24 students of TOEFL Program which was divided into 3 classes, A, B, and C. In collecting the data, the writer did the process of distributing the questionnaires and putting them into a table. Then, the writer analyzed the data by calculating it using computer application called Statistical Product and Service Solution (SPSS).The result showed that the types of motivation used by the students at TOEFL Program of ELFAST English Course in Pare was instrumental motivation and integrative motivation and the primary types of motivation among the students at TOEFL program of ELFAST English Course in Pare was instrumental motivation.Related to the relationship between motivation and students’ TOEFL scores, thepositive significant correlation is revealed between motivation and students’ Englishproficiency measured by TOEFL final scores.From this study, the writer suggests the future researchersto conduct a research regarding motivation in learning English by using instrument Attitude/Motivation Test Battery (AMTB) questionnaire while collecting the data and explore more reason items of motivation from the questionnaire.The future researchers can also expand the motivation research and correlated it with other fields in second language learning. It might be correlated with learning strategy, learning style, or others